The magic of seaweed (Ascophyllum nodosum) extract in influencing the dynamics of yield, quality, and storage behavior of garlic - Mandal, Aniket; Sharangi, Amit Baran; Al-Keridis, Lamya Ahmed; Rab, Safia Obaidur; Alshammari, Nawaf; Saeed, Mohd; Alshammari, Mamdouh; Alabdallahd, Nadiyah M. (Frontiers in Plant Science, 2025)
IntroductionSince prehistoric times, garlic is one of the leading spices extensively cultivated for its flavour, pungency and medicinal values. Organo sulphur compounds viz., Allicin and diallyl disulfide are responsible for numerous medicinal properties. Among quite a few natural and synthetic substances, biostimulants have rewarding effects on garlic growth, stress tolerance, yield and productivity. Ascophyllum nodosum (seaweed) is such an inimitable biostimulant extensively used in garlic.Materials & MethodsThe current study was conducted during two years at BCKV-Agricultural University, India to evaluate the effect of A. nodosum. Six different garlic genotypes including one local variety Goldana and 3 doses of A. nodosum were considered to study various morphological, yield attributing and quality parameters and their inter relationship with weather variables and the storage behaviour.Results and DiscussionThe experiment revealed that AVT-1GNB-23-41 was the best among all the genotypes. The treatment AVT-1GNB-23-41×seaweed@1ml/L gave the maximum plant height (73.07cm),leaf width(2.32cm), polar & equatorial diameter (35.45, 36.33mm),clove length (2.64 cm), cloves/bulb (30.95), weight of bulb (18.87g), total yield (7.02t/ha) compared to others. AVT-1GNB-23-41 genotype showed highest TSS (30.83°Brix), phenol (159.65mg GAE/100g) while ascorbic acid (14.74mg/100g) was maximum in AVT-1GNB-23-26. In case of correlation study, bright sunshine hours and total rainfall had positive and negative correlations with total yield. L* and b* values decreased with advancement of storage but a* value was increased upto certain time and then decreased. On storage point of view, the treatment AVT-1GNB-23-47×seaweed@1ml/L was superior with lowest physiological weight loss at 36 DAST.